Integrasi Sains dan Islam dalam Pembelajaran Madrasah: Analisis Pedagogis Pendekatan Integralistik dalam Studi Islam - Afrizal Afrizal; Taslim Perdana; Nurnajmi Nurnajmi; Rosniati Hakim; Sri Wahyuni (MAN 4 Kota Pekanbaru, 2025)
The dichotomy between religious and secular sciences has long been a challenge within the Islamic education system, particularly in madrasahs. Consequently, teaching practices often become fragmented and disconnected from the spiritual dimension of Islam. This article aims to conceptually examine the importance of an integralistic approach in Islamic Studies as an epistemological foundation for integrating science and Islam in madrasah education. The study employs a library research method using content analysis of classical and contemporary Islamic scholars such as Amin Abdullah, Fazlur Rahman, Ismail Raji al-Faruqi, and Zakiyuddin Baidhawy. The findings indicate that the integralistic approach facilitates an epistemological dialogue between revelation, reason, and empirical reality, allowing madrasah learning to integrate the values of tawhid with modern scientific knowledge. Hence, the integration of science and Islam is not merely a curricular synthesis but a paradigm shifts that positions knowledge as an act of devotion to God. The study recommends developing a curriculum model based on integrative-interconnective approaches and strengthening teachers’ competencies to foster holistic and transformative learning.